Effects of Resveratrol on Methotrexate-Induced Testicular Damage in Rats. (28th July 2013) - Yuluğ, Esin; Türedi, Sibel; Alver, Ahmet; Türedi, Süleyman; Kahraman, Cemil
Abstract : This study investigated the probable protective effects of resveratrol (RES), an antioxidant, against methotrexate- (MTX-) induced testis damage. Twenty-four male Sprague Dawley rats were randomly divided into four groups: control, RES, MTX, and MTX + RES groups. Rats were sacrificed at the end of the experiment. Plasma and tissue malondialdehyde (MDA) levels, superoxide dismutase (SOD) and catalase (CAT) activity in tissue, testicular histopathological damage scores, and testicular and epididymal epithelial apoptotic index (AI) were evaluated. The MTX group had significantly higher plasma and tissue MDA levels and significantly lower SOD and CAT activity than those of the control group. In the MTX + RES group, plasma and tissue MDA levels decreased significantly and SOD activity rose significantly compared to the MTX group. The MTX group had significantly lower Johnsen's testicular biopsy score (JTBS) values than those of the control group. JTBS was significantly higher in the MTX + RES group than in the MTX group. AI increased in the testis and epididymis in the MTX group and significantly decreased in the MTX + RES group. Our results indicate that RES has protective effects against MTX-induced testis damage at the biochemical, histopathological, and apoptotic levels.